The Effect of Using Scaffolding Technique on the Competency in Writing Descriptive Text at the Eighth Grade of Mts Negeri Srono in Academic Year 2015/2016 - ., Putri Dito Rembulan; ., I Nyoman Pasek Hadi Saputra, S.Pd., M.Pd; ., Kadek Sonia Piscayanti, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This study aimed at investigating whether or not there was a significant difference between the students’ writing competency in writing descriptive text taught by using Scaffolding Technique and Conventional Teaching Technique. Post test only control group design was applied in this study. The population of this study was the eighth grade students at MTs Negeri Srono. Through cluster random sampling, VIIIG class and VIIIH class were taken as the samples of this study. Then, by implementing a lottery technique, it was determined that VIIIG was assigned as experimental group and VIIIH as the control group. The experimental group was taught by using Scaffolding Technique, while the other group was taught by using Conventional Teaching Technique. The data were obtained from posttest and were analyzed by using descriptive statistic analysis as well as inferential statistic analysis. The result of posttest shows that the experimental group obtained better achievement than the control group. It was proven by the mean score of the experimental group was 84.46 while the mean score of the control group was 71.94. Moreover, the result of the inferential statistic analysis show the value of t observed (tobs) 5.977 higher than the critical value of t (tcv) which was 2.0395 at 0.05 significant levels. It indicates that the null hypothesis (Ho) in this study was rejected while the alternative hypothesis (Ha) was accepted. This proved that there was a significant difference in the students’ writing competency in writing descriptive text taught by using Scaffolding Technique and Conventional Teaching Technique.Kata Kunci : Writing Competency, Scaffolding Technique, Descriptive Text Penelitian ini bertujuan untuk menyelidiki apakah ada atau tidaknya perbedaan yang signifikan antara kompetensi menulis siswa dalam menulis teks deskriptif yang diajarkan dengan menggunakan teknik Scaffolding dan pengajaran teknik konvensional. Posttest only control desain diterapkan dalam penelitian ini. Populasi dari penelitian ini adalah siswa kelas delapan MTs Negeri Srono. Melalui cluster random sampling, kelas VIIIG dan kelas VIIIH diambil sebagai sampel penelitian ini. Kemudian, dengan menerapkan teknik undian, ditetapkan bahwa VIIIG dipilih sebagai kelompok eksperimen dan VIIIH sebagai kelompok kontrol. Kelompok eksperimen diajar dengan menggunakan teknik Scaffolding, sedangkan kelompok lainnya diajarkan dengan menggunakan Pengajaran Teknik Konvensional. Data diperoleh dari posttest dan kemudian dianalisis dengan menggunakan analisis statistik deskriptif serta analisis statistik inferensial. Hasil posttest menunjukkan bahwa kelompok eksperimen memperoleh nilai yang lebih baik daripada kelompok kontrol. Hal ini dibuktikan oleh nilai rata-rata dari kelompok eksperimen adalah 84,46 sedangkan nilai rata-rata dari kelompok kontrol adalah 71,94. Selain itu, hasil analisis statistik inferensial menunjukkan nilai t observed (tobs) 5,977 lebih tinggi dari nilai t critical value (tcv) yaitu 2,0395 pada tingkat signifikan 0,05. Hal ini menunjukkan bahwa hipotesis nol (Ho) dalam penelitian ini ditolak sedangkan hipotesis alternatif (Ha) diterima. Ini membuktikan bahwa ada perbedaan yang signifikan dalam kompetensi menulis siswa dalam menulis teks desktiptif yang diajarkan dengan menggunakan teknik Scaffolding dan pengajaran teknik konvensional.keyword : Kompetensi Menulis, Teknik Scaffolding , Teks Descriptif